Student Participation in Physical Education Learning: A Study at SMA Negeri 2 Sinjai - Juhanis Juhanis (Journal of Physical Education, Sport, and Human Performance, 2026)
This study aims to analyze the level of student participation in physical education learning at SMA Negeri 2 Sinjai. Student participation is an important indicator in determining the success of the learning process, especially in educational subjects that emphasize aspects of physical, cognitive, and affective involvement. This study uses a quantitative descriptive approach with a survey method. The research sample consisted of 120 students randomly selected from grades X and XI. The instrument used was a student participation questionnaire that had been tested for validity and reliability. Data were analyzed using descriptive statistics in the form of percentages. The results showed that student participation in physical education learning was highest in the affective (72%) and psychomotor (68%) aspects, which reflected active involvement and positive attitudes of students towards learning activities. However, participation in the cognitive aspect is still relatively low (60%), so a strategy is needed to improve students' understanding and involvement intellectually. Student participation is influenced by interest, motivation, learning methods, availability of facilities, social support, and self-confidence. These findings indicate the need for more varied and participatory learning strategies to increase student involvement in physical education.